Anticoccidial activity of Artemisinin and Extract of Artemesia annua leaves in chicken infected by Eimeria tenella - Ening Wiedosari; April Hari Wardhana (Jurnal Ilmu Ternak dan Veteriner, 2017)
The continuous use of anticoccidial drug in chicken often continuously generates drug resistance and tissue residue; so thatconsequently, a safe alternative anticoccidial drug based on herb is fundamentally required. The aim of thise study was to examine anticcocidial activity of artemisinin and extract of Artemesia annua leaves in chicken infected by Eimeria tenella. A total of 35 chickens of Cobb strain was divided into seven groups with five replicates birds per group, i.e. uninfected chicken group (P I), infected but untreated chicken group (P II), infected and treated chicken group with 8.5 ppm, 17 ppm, 34 ppm, for P III, P IV and P V respectively, infected and treated chicken with 17 ppm of A. annua extract (P VI) and infected and treated chicken with Sulfa (P VII). All chicken, except the uninfected group, whereas infected with 2000 infective oocyst of E. tenella except the uninfected group. Treatment was delivered by oral, once per day for eight days. The criteria observed were clinical manifestation of chickens, number of oocyst in feces, body weight, cecal lesion score, haematocrit (packed cell volume) and haemoglobin value. The results showed that extract of A. annua leaves (P VI) was the most effective treatment to reduce the number of oocyst in feces (74.18%), followed by 34 ppm of artemisinin group (P VII). In addition, application of A. annua extract and artemisinin was significantly able to decreased the cecal lesion score (P<0.05). Even though body weight and Hb value were not indifferent significantly different (p>0.05), however A. annua extract and artemisinin treatments were significantly able to hold PCV value on normal level compared to P II and P IV (P<0.05). It concluded that extract A. annua leaves and artemisinin could be used an alternative anticoccidial in chickens.